Model Matematis Penentuan Lokasi Potensial Pos Bantuan atau Depo Bencana Banjir di Kabupaten Gresik - Sugiarto, Sonny; Widyadana, I Gede Agus; Octavia, Tanti (Jurnal Titra, 2015)
This research was conducted to determine the location of potential aid depot at the time of the annual flood disasters in Gresik Regency. Determination of the location of potential aid depot is applied using mathematical models and involving BPBD of East Java and BPBD Gresik. Linear programming is applied and solved using solver excel software. The constraint of this mathematical model made are time constraint, the number of vehicles, dan the amount of potential aid depot. The function of the purpose of mathematical model is abaout handling maximize the number of victims dan minimized the total time of delivery relief. The result of research shows that to determine the location of potential assistance or post depot influenced by some obstacle that is the time constraint, the number of vehicles, and the objective function.